Anti-tissue transglutaminase antibodies not related to gluten intake - Mónica Garcia-Peris; Ester Donat Aliaga; María Roca Llorens; Etna Masip Simó; Begoña Polo Miquel; Carmen Ribes Koninckx (Elsevier, 2018)
Introduction: Anti-tissue transglutaminase antibodies (tTG) have high specificity for coeliac disease (CD). However, positive anti-tTG antibodies have been described in non-coeliac patients. Aim: To assess positive anti-tTG antibodies not related to gluten intake. Patients and methods: Retrospective review and follow up conducted on patients with suspected CD (increase anti-tTG levels and gastrointestinal symptoms) but with atypical serology results, positive anti-tTG with gluten free diet and a decrease in anti-tTG levels despite gluten intake. Results: A total of 9 cases were reviewed in which 5 cases had Marsh 3 involvement in the initial biopsy, and were diagnosed with CD (Group A). They began a gluten free diet and also a cow's milk protein (CMP) free diet because of their nutritional status. When CMP was re-introduced, anti-tTG increased, and returned to normal after the CMP was withdrawn again. The other 4 patients had a normal initial biopsy (Group B). Gluten was not removed from their diet, but they started a CMP free diet because a non IgE mediated CMP allergy was suspected. Symptoms disappeared, and anti-tTG was normal after CMP free diet with gluten intake. All the patients had susceptibility haplotype HLA DQ2/DQ8. Conclusions: CMP ingestion after an exclusion diet can induce an increase in anti-tTG in some coeliac subjects. CMP can produce this immune response if there were no gluten transgressions. This response has also been observed in non-IgE mediated CMP allergy patients with the susceptibility haplotype HLA DQ2/DQ8. Resumen: Introducción: Los anticuerpos antitransglutaminasa (ATG) poseen alta especificidad para el diagnóstico de enfermedad celíaca (EC). Sin embargo, se han descrito anticuerpos ATG positivos en pacientes no celíacos. Objetivo: Valorar la presencia de anticuerpos ATG positivos no relacionados con la ingesta de gluten. Pacientes y métodos: Revisión retrospectiva de historias clínicas y seguimiento de pacientes con sospecha de EC y con un comportamiento serológico atípico, es decir, anticuerpos ATG positivos a pesar de una dieta sin gluten y disminución de anticuerpos ATG tomando gluten. Resultados: Se incluyeron 9 casos. De ellos, 5 casos tenían afectación histológica Marsh 3 en la biopsia inicial y diagnóstico de EC (grupo A). Se retiró el gluten de la dieta y se retiraron las proteínas de leche de vaca (PLV) por la afectación nutricional. Al reintroducir las PLV aumentaron los ATG y al retirarlas se volvieron a normalizar. Los otros 4 pacientes presentaban una biopsia inicial normal (grupo B): en estos no se retiró el gluten, pero sí las PLV por sospecha de alergia no IgE mediada. Los síntomas desaparecieron y se normalizaron los ATG al retirar las PLV manteniendo dieta con gluten. Todos presentan el haplotipo de susceptibilidad para EC. Conclusiones: En algunos celíacos, la reintroducción de PLV en la dieta tras un período de exclusión induce un aumento de los anticuerpos ATG IgA. Si se han descartado transgresiones con gluten, las PLV pueden causar esta respuesta inmune. Hemos observado también esta respuesta en pacientes con alergia no IgE, mediada por las PLV, portadores del haplotipo de susceptibilidad HLA DQ2/DQ8.